Digital Edukasi Tentang Body Shaming Pada Remaja Berbasis Website - Ketut Gus Oka Ciptahadi; Vandya Rahmayani, Nabila (Jurnal Ilmiah Binary STMIK Bina Nusantara Jaya, 2022)
Body shaming is criticizing or making negative comments on someone's physical form intentionally or not. Teenagers can be called people who are very vulnerable to being affected by body shaming, because teenager is a period where they try to develop themselves, find identity, so that the trend regarding beauty standards that is rife on social media will influence their thinking. There is a problem that many people do not know about the negative impact of body shaming that will happen to teenagers. Based on these problem, an Digital Education about body shaming on Teenager Website Based was made. Presented more attractively using Website-based Learning Multimedia which is expected to be able to educate the wider community about Body Shaming. This application was built by applying the Multimedia Development Life Cycle method. This application is designed using Adobe Photoshop. Adobe Animate, Adobe Premiere Pro, and Adobe Audition. Application testing uses 2 methods, consisting of Blackbox Testing, Questionnaire. The result of this application is in the form of an application that contains information about body shaming that is presented with an attractive appearance by including all multimedia elements in it. Based on questionnaire testing that has been conducted on 30 respondents, the average result is 4.6 with a percentage of 92%, it can be concluded that the application “Digital Education About Body Shaming on Teenager Website Based” has been made “Very Good”. Keywords: Body shaming, Teenager, Digital Education, Multimedia Applications